Foucault's 1960s Lectures on Sexuality. (January 2023) - Downham Moore, Alison; Elden, Stuart
In this extended review essay we discuss the lectures on sexuality which Foucault delivered in the 1960s, published in a single volume in 2018. The first part of the volume comprises five lectures given at the University of Clermont-Ferrand in 1964 to psychology students. The second part is Foucault's course 'The Discourse of Sexuality', given at the experimental University of Vincennes in 1969 in the philosophy department. We explore both the themes of the lectures, and the important editorial materials provided by Claude-Olivier Doron which situate these themes in relation to recent developments in the history and philosophy of biology, gender and sexuality. These lectures provide some important and surprising additions to Foucault's more familiar interest in sexuality, with discussion of plant and animal biology, sex differentiation, the question of sexual behaviour, perversion and infantile sexuality.